Dionysus and the land of beasts - West, Tracey, 1965- (Heroes in training, 2017)
With a clue from the oracle Pythia, the Olympians head to the Land of Grapes where they encounter Dionysus, who they suspect is also an Olympian with great powers, but he could turn out to be a hindrance in their attempt to dethrone King Cronus.